The Spring of Our Discontent: Catullus 46 and the Classical Spring Poem - Dorin Garofeanu (Revista de Istorie și Teorie Literară)
Although Catullus 46 has been occasionally referred to or described as a spring poem, this generic aspect has been either largely ignored or somewhat superficially treated. This article provides a detailed analysis of the poem, revealing the numerous thematic, structural and stylistic similarities to the chronologically earlier spring poems included in the Palatine Anthology (A.P. 10.1 and 2) that suggest that Catullus is deliberately drawing upon the Greek tradition of the genre. This close reading of the poem will also show the effort and ingenuity with which Catullus, while preserving the traditional structure and some of the conventional elements, reshaped the genre and invested it with a psychological dimension and complexity unknown to the Greek tradition.